The effects of Voluntary Sustainability Standards in the economy of smallholder farmers in Latin America: An investigation of the impact pathways of sustainability standards leading to improved economic outcomes for certified coffee producers - Estrella, Andrea (2020)
This dissertation attempts to answer the following questions:(1) What is the economic impact of different certifications in smallholder coffee farmers; (2) What are the “mechanisms” or “pathways” leading to higher economic returns in certified smallholder coffee farmers; and (3) How are the analyzed certifications performing in these impact pathways?I develop a theoretical model based on impact pathways to determine whether voluntary sustainability standards lead to economic development for small coffee farmers in Latin America. The dataset used for this analysis comprises of cross-sectional data from three countries Colombia, Costa Rica and Honduras. I employ Propensity Score Matching and regression analysis, combined with sensitivity analyses such as Rosenbaum bounds. Each certification is assessed separately against a pool of controls to arrive at the disaggregated effects of each standard. The results suggest that certifications have very limited effects on farmer profitability.Permalink https://nbn-resolving.de/urn:nbn:de:hbz:6-41119437684ISBN978-3-8405-0234-7Paperback, 219 Seiten